Enhancing High School Students Investment Skills and Risk Management Through Capital Market Simulation with Virtual Trading - Mauliana Wayudi; Rizki Aria; Aidil Akbar; Raisah Raisah; Sarah Adilla (LPPM STKIP Kusuma Negara, 2026)
This study examines the effectiveness of virtual trading–based capital market simulations in improving high school students’ investment and risk management skills, addressing the persistently low level of financial literacy among Indonesian adolescents. Using a quantitative approach with a quasi-experimental nonequivalent control group design, this research involved an experimental group that learned through virtual trading simulations and a control group that received conventional instruction. Data were collected through pretests and posttests and analyzed using normality and homogeneity tests, paired sample t-tests, and ANCOVA (a = 0.05). The results indicate that students who participated in virtual trading simulations experienced a significantly greater improvement in investment and risk management skills than those in the conventional learning group. These findings suggest that simulation-based learning enhances students’ critical and practical thinking by providing experiential exposure to real-world investment decision-making. Accordingly, integrating virtual trading simulations into economic education can serve as an effective instructional strategy to better prepare students for real-life financial challenges. However, this study has limitations in terms of contextual scope, as it was conducted in only one school, which may affect the generalizability of the findings to broader educational settings.